Protecting grapevines from rainfall in rainy conditions reduces disease severity and enhances profitability. (January 2015) - Du, Fei; Deng, Weiping; Yang, Min; Wang, Haining; Mao, Ruzhi; Shao, Jianhui; Fan, Jinxiang; Chen, Yunde; Fu, Yang; Li, Chengyun; He, Xiahong; Zhu, Youyong; et al.
Abstract: The growing season of grapes is often associated with high levels of rainfall in the Chinese rainy regions, which leads to serious grape diseases. In this study, we sheltered grapevines from rainfall for the purpose of disease management. Experimentally (2007 and 2008), it was found that rain shelter could block the rainfall and clearly reduced the average daily leaf wetness duration and the relative humidity in the canopy compared with open field cultivation. The average severities of grape ripe rot, white rot, downy mildew, grey mould, and brown spot on the Red Globe cultivar were reduced by 85, 73, 81, 54, and 68% compared with fungicide sprays. The average severities of grape ripe rot, white rot, grey mould, and brown spot on the Shuijing cultivar were reduced by 84, 65, 100, and 73% compared with fungicide sprays. Rain shelter increased grape yields by an average of 110–176% and increased farmers' income by an average of 80–193% compared to fungicide sprays. Large-scale field monitoring from 2009 through 2012 unequivocally confirmed that rain shelter could effectively and stably control the main grape diseases. Although powdery mildew infections were more severe in plants under rain shelter cultivation than in plants under open field cultivation, this disease could be effectively controlled by one application of prochloraz and one application of difenoconazole during the growing season in vineyard trials under rain shelter from 2011 through 2013. These results demonstrated that protecting grapevines from rainfall is an efficient disease management technique with extensive application prospects in rainy regions. Graphical abstract: Highlights: Canopy microclimate was modified when grapes were cultivated under rain shelter. Rain shelter effectively and stably controlled the main grape diseases in southern China. Powdery mildew was controlled by rain shelter combined with fungicide application.